2015
DOI: 10.1016/j.forsciint.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation of gasoline in soil: Effect of season of sampling

Abstract: In cases where fire debris contains soil, microorganisms can rapidly and irreversibly alter the chemical composition of any ignitable liquid residue that may be present. In this study, differences in microbial degradation due to the season in which the sample is collected was examined. Soil samples were collected from the same site during Fall, Winter, Spring and Summer and the degradation of gasoline was monitored over 30 days. Predominant viable bacterial populations enumerated using real-time PCR and revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
0
15
0
3
Order By: Relevance
“…Beside these, there is low‐risk microbiological contamination in winter due to soils and gasoline was affected by microbial degradation during winter (Turner et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Beside these, there is low‐risk microbiological contamination in winter due to soils and gasoline was affected by microbial degradation during winter (Turner et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, reducing the exposure of cows to the natural environment by housing them in sheds where they are fed hay during late autumn and winter could be an important factor for the reduced B. cereus contamination levels in raw milk during this time of year (Bartoszewicz et al 2008). Beside these, there is low-risk microbiological contamination in winter due to soils and gasoline was affected by microbial degradation during winter (Turner et al 2015).…”
Section: Risk Factors Associated With the Prevalence Of Bacillus Cerementioning
confidence: 99%
“…Since the oil-based paints are made up of a wide range of hydrocarbons, media enriched with oil-based paints serve as a rich source of carbon and energy for several microbial species [17]. Although several factors affect bacterial numbers and activities in soil, including soil type and season [17], only a few studies in the literature have addressed the removal of oil-based paints and/or paintrelated waste materials from paint-polluted environments [1].…”
Section: Introductionmentioning
confidence: 99%
“…Although several factors affect bacterial numbers and activities in soil, including soil type and season [17], only a few studies in the literature have addressed the removal of oil-based paints and/or paintrelated waste materials from paint-polluted environments [1]. In the present study, an indigenous oil-based paint utilizing the bacterial strain of B. parabrevis was isolated and characterized from oil-based paint polluted soil samples and assessed for the biodegradation of oil-based paints in aqueous media using a shake flask experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Unambiguous detection of reformate in fire debris samples can therefore be problematic, especially in cases of relative low amounts of gasoline, when other petroleum products are present and/or in the presence of pyrolysis products from certain polymers. Gasoline cannot be distinguished from aromatic solvents on the basis of the presence of aromatic compounds alone. The additional requirement that alkanes should be present is rather unspecific and cannot convincingly make the distinction in all cases . Studies on the microbial degradation of gasoline compounds in samples containing soil have shown that aromatic compounds are vulnerable to microbial degradation and that the monosubstituted benzenes in particular are the most vulnerable . Microbial degradation therefore leads to distorted aromatic profiles, which might not be recognized as originating from reformate. Reformate can be used as a source for specific aromatic compounds that can be extracted from it in the refinery , resulting in an altered composition that is used for gasoline blending, which might not be recognized as originating from reformate. Gasoline brands are sold that do not contain reformate, such as Aspen and Cleanlife.…”
mentioning
confidence: 99%